Translation Techniques in Adapting AKB48 Japanese Songs into JKT Indonesian Versions - Priscilla Nazar, Andrea Clarissa; Setiawan, Hari; Hendriati, Riri (Chi e Journal of Japanese Learning and Teaching, 2025)
This study examines the translation techniques used by Rininditha Pradiza in adapting AKB48 song lyrics into their Indonesian versions for JKT48. Using a descriptive qualitative approach based on Molina and Albir’s (2002) translation techniques framework, this study analyzes four songs: Heavy Rotation, Kimi No Koto Ga Suki Dakara (Because I Like You), Ponytail to Chou-Chou (Ponytail and Butterfly), and Baby! Baby! Baby! The data were collected through text analysis and online interviews with the translator. The analysis process involved data reduction, presentation in tables and narratives, and the identification of translation technique patterns. The findings revealed that the Literal Translation Technique is the most frequently employed (55%), followed by Borrowing (24%), Amplification (13%), and Modulation (8%). The literal translation technique preserves the original sentence structure while Borrowing retains familiar words from the source language. The amplification techniques add explanatory elements, and the modulation technique alters perspectives to enhance naturalness in the target language. This study concludes that the choice of translation techniques significantly influences the readability and semantic appropriateness of the lyrics in Indonesian.